Fermentasi Biji Kakao Kering Menggunakan Saccharomyces cerevisiae, Lactobacillus lactis, dan Acetobacter aceti - Mulono Apriyanto; Sutardi Sutardi; Supriyanto Supriyanto; Eni Harmayani (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
The aims of the study was to improve quality of cocoa bans by fermentation of sun dried cocoa beans. The fermentation variations were conducted as follows: first, fermentation without the addition of inoculum (control), the second treatment using inoculum of S. cerevisiae (FNCC 3056), L. lactis (FNC 0086) and A. aceti (FNCC 0016), each of 108 cfu/g given simultaneously at the beginning of fermentation.and the third treatment wassequential administration, i.e: yeast at the initial fermentation, lactic acid bacteria after 24 hours fermentation, and acetic acid bacteria after 48 hr of fermentation third with the same microbial population with the second treatment. The fermentation was conducted for120 hours. The fermentation temperature were controlled during fermentation as follows: 35 °C for the first 24 hours, 45 °C for the next second 24- hours, 55 °C the third 24 hours and 35 °C for the last 48 hours of fermentation. The results showed that after the rehydration, pulp composition of dry beans could be used as a substrate for fermentation. During fermentation, dry cocoa beans showed reduction of total sugar content, pH and total polyphenols for all the three treatments. Cut test of dried cocoa beans during the fermentation showed the increasing percentage of brown color of the three treatments. Reducing sugar and fermentation indexes increasedfor all treatments during fermentation. Concentration of ethanol, lactic acid and acetic acid reached highest level at 24, 60, and 108 hours of fermentationfor all treatments. Highest populations of S. cerevisiae, L. lactis and A. aceti of three treatments obtained at 24, 48 and 72 hours of fermentation. After fermentation and roasting, dry beans produced hydrophobic amino acids as precursors of flavor and volatile compounds. ABSTRAKPenelitian ini bertujuan untuk mengetahui perubahan sifat kimia pada fermentasi biji kakao kering jemur. Biji kakao kering jemur yang diperoleh dari petani memiliki kadar air yang tidak seragam. Guna menimalkan kegagalan fermentasi maka biji kakao kering jemur diperoleh melalui pengeringan biji kakao segar menggunakan kabinet dryer dengan sebelumnya dikondisikan pada suhu seperti pengeringan dengan sinar matahari, dan masing ditentukan kadar gula reduksinya. Percobaan fermentasi biji kakao kering dilakukan fermentasi pada wadah fermentasi dengan jumlah biji 150 g setiap wadah. Sebelum difermentasi terlebih dahulu biji kakao kering jemur direhidrasi agar didapat kadar air mendekati biji segar, kemudian biji kakao kering jemur diinkubasi selama enam hari dan tanpa dibalik selama fermentasi. Setiap perlakuan diulangi tiga kali dan diamati tiap 24 jam sampai 120 jam. Kadar gula reduksi (kontrol 4,49–11,45%, inokulum diawal (IA) 4,69–11,55%, inokulum bertahap (IB) 4,64–11,54%), kadar asam tertitrasi (kontrol 4,48–6,45%, inokulum diawal (IA) 4,64–6,39%, inokulum bertahap (IB) 4,45–6,59%), populasi Saccharomycescerevisiae (kontrol 5,56–7,28 (log CFU/g), inokulum diawal (IA) 6,45–8,75 (logCFU/g), inokulum bertahap (IB) 6.88 – 8.99 (logCFU/g), Lactobacillus lactis (kontrol 6,66–8,15 (log CFU/g), inokulum diawal (IA) 7,65–8,21(log CFU/g), inokulum bertahap (IB) 7,66–8,95 (log CFU/g) dan Acetobacter aceti (kontrol 4,26–6,95% (log CFU/g), inokulum diawal (IA) 4,85–7,40 (log CFU/g), inokulum bertahap (IB) 4,35–7,91 (log CFU/g)) dalam pulp fermentasi diamati selama proses fermentasi. Untuk mengetahui kualitas biji kakao dilakukan pengukuran pH (kontrol 5,67–3,98, inokulum diawal (IA) 5,67–3,55, inokulum bertahap (IB) 5,67–3,50), kadar etanol (kontrol 0,3–0,5%, inokulum diawal (IA) 0,3–0,52%, inokulum bertahap (IB) 0,35–0,53%) dan indeks fermentasi selama fermentasi (kontrol 0,31–0,88, inokulum diawal (IA) 0,32–0,99, inokulum bertahap (IB) 0,33–1,03).Kata kunci: Acetobacter aceti; biji kakao kering jemur; fermentasi; Lactobacillus lactis; Saccharomyces cerevisiae